(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The integration of online learning into mining-related education offers significant advantages in terms of accessibility and flexibility. Online learning expands access to specialised education, allowing students from diverse regions to participate without the need to relocate or attend in-person classes. By offering online courses, educational institutions can ensure that students receive up-to-date knowledge, preparing them to address both traditional and emerging challenges in the mining industry. Online platforms provide students with access to a variety of resources, such as lectures, research papers, and interactive simulations, which enhance their understanding of complex mining processes. However, it can be challenging for teachers to engage students online and gauge their level of engagement. Online engagement can be perceived differently than in-class engagement. This article explores interactive learning, which combines online education with hands-on experiences. Students engage in real-world measurements, create models, and apply these models in classroom activities. Online learning promotes self-directed study and offers flexibility. Onsite learning, in turn, allows students to apply theoretical knowledge in practical settings, fostering critical thinking and problem-solving skills. By combining both online and onsite learning, students benefit from a comprehensive educational experience that enhances technical expertise and creativity, ultimately improving learning outcomes.